Morphometrics of Facies Patellaris Femoris in Dry Bones - Aksu, Feyza; Akkoc, Ramazan Fazil (Springernature, 2023)
Introduction: The aim of this study was to investigate the morphological features of the distal femur, with a specific focus on the facies patellaris femoris.Methods: A total of 45 dry femurs from adult individuals (24 right, 21 left) were used for the study. Measurements were taken using a calibrated digital vernier caliper and a contour gauge.Results: Anteroposterior (AP) measurements were taken for the medial and lateral condyles of the femur, as well as the articular surfaces of the facies patellaris, sulcus height (51.186 +/- 3.81mm), trochlear depth (7.436 +/- 1.19mm), and trochlear index (2.295 +/- 0.06mm). The results showed that the width of the facies patellaris had a significant positive correlation with the trochlear depth and trochlear index. The length of the facies patellaris was positively correlated with the AP length of the medial condyle and sulcus height, although it was not statistically significant. Additionally, there was a statistically significant positive correlation between the length, width, and medial and lateral articular surfaces of the facies patellaris (p<0.005).Conclusion: Understanding the relationship between the morphometry of the medial and lateral condyles of the distal femur and the morphometry of the facies patellaris, sulcus height, trochlear depth, and trochlear index and examining the anatomy of the distal femur and patella in individuals are crucial factors for determining appropriate medical treatment and implant selection and compatibility. The findings of this study are expected to contribute to clinicians' interventions in this region (total knee arthroplasty/replacement operation etc.). These data can also be used by implant designers and forensic experts during investigations.
Keywords: morphometry; distal femur anatomy; trochlear index; trochlea; facies patellaris